Nutrition in institutions - Cross, Maria; MacDonald, Barbara (Wiley-Blackwel, 2009)
The importance of good nutrition for individual health and well-being is widely recognized, yet for a significant number of people who rely on institutions for food and nutrition, this importance has not always been a primary consideration.